O uso da rede de proteção na produção de produtos de moda - Costa, Paola Cristinne Guimarães da (2017)
The present project aims to study the application of construction the application of the Construction and Demolition Network (CDN), derived from civil construction planning, in the design of fashion products. Based on bibliographical and experimental research, the project intends to developnpieces with innovation in the materialbut with a fashionable content that makes possible it’s commercialization for the youg fashion and avant-garde public. For this purpose, a theoretical study of the construction, material disposal, construction waste, characteristics and use of waste, pertinent legislation, sustainnability, creative thinking and fashion reasearch will be carriet out. As a mais result, it is hoped develop a 2018 winter collection, created under the upcycling tools for the brand created during the study, that contain pieces of protection screeen and that meet a standard of quality and aesthetics necessary for the initiave to be carried forward.